Exploring Vocabulary Learning Strategies in EFL: A Case Study of Sudanese University Students - Amel Zulfukar Hassan Adlan; Eko Risdianto (Indonesian Journal of Pedagogy and Teacher Education, 2026)
Background: Sudanese University students face significant challenges in English proficiency due to historical Arabicization policies and outdated pedagogical frameworks. While vocabulary is a primary predictor of linguistic success, a systemic gap exists between strategy awareness and long-term lexical retention. Aims: This study investigated the relationship between Vocabulary Learning Strategies (VLS), institutional support, and actual proficiency (receptive and productive) among Sudanese undergraduates. Methods: Using s triangulated quantitative and documentary design ($N=240$), the study utilized the Vocabulary Levels Test (VLT), Lex30, a Likert-scale VLS questionnaire, and a systematic analysis of university syllabi. Data were analyzed using Structural Equation Modelling (SEM) and psychometric validation. Results: Psychometric tools demonstrated strong internal validity ($\text{VLT } α = 0.86$; Lex30 $M = 14.2/30$). Latent profile analysis revealed a severe "Knowledge-Application Gap": 64% of students possess theoretical awareness of exploratory strategies, yet 30% of the total sample occupy an "Overlap Group" experiencing persistent lexical acquisition failures. SEM confirmed that while discovery strategies predict receptive ($β = 0.35$) and productive ($β = 0.29$) outcomes, consolidation strategies are the strongest predictors of productive mastery ($β = 0.41$). Crucially, institutional support moderates strategy effectiveness by 18% ($β = 0.18$). Documentary analysis revealed that 83% of syllabi ignore explicit strategy instruction entirely, and 0% feature systematic spaced-retrieval tasks. Conclusion: The findings demonstrate that individual learner strategic awareness is heavily suppressed by a systemic instructional vacuum. Sudanese university curricula are overwhelmingly biased toward passive word recognition, failing to provide the structured consolidation routines required to transition vocabulary from short-term memory into active communicative competence. Rectifying this deep-seated proficiency gap requires immediate curriculum reform, institutionalized strategy modeling, and the integration of low-bandwidth, offline-capable digital learning tools.